The Influence Of Service Quality And Facilities On Customer Satisfaction At The Meeting Package At The Grand Savero Hotel Bogor - Rachmananda, Jordan Farhan; Manurung, Tarida Marlin Surya; Rainanto, Bambang Hengky (Jurnal Ilmiah Pariwisata Kesatuan, 2024)
In the current modern era, the development of the hotel business in the city of Bogor has increased greatly, causing competition for hotels to attract consumers. One form of strategy to increase the length of room occupancy rate is to focus on Bleisure Travel or a combination of business and leisure (vacation). Bleisure Travel has become a popular trend recently considering the increasing development of globalization. So a meeting package was created provided by hotels in big cities to support this activity. This research aims to analyze the influence of Service Quality and Facilities on consumer satisfaction with meeting packages at the Grand Savero Hotel Bogor.. This research is a quantitative research and the population in this research is all people aged 17 years and over and have used meetings packages at the Grand Savero Hotel Bogor. The sampling technique uses purposive sampling with a sample size of 100 respondents. The data source used is primary data in the form of data collection using questionnaires that are distributed directly. The analysis method is validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression analysis. , t test, F test, and coefficient of determination R Squared. With a significance level of 0.05 using IBM SPSS 25 and Microsoft Excel software. The results of the research show that: (1) Service Quality has a positive and significant effect on Consumer Satisfaction (t count : 3.143; significance: 0.002<0.05; and β: 0.283), (2) Meeting package facilities have a positive and significant effect on Customer Satisfaction (t count: 6.637; significance: 0.000<0.05; and β: 0.597), and (3) Service Quality and Facilities simultaneously have a positive and significant effect on Consumer Satisfaction (F count: 114.650 and significance 0.000< 0.05). The coefficient of determination test results shown is adjusted R2 which is 0.697. This shows that the uniformity of Consumer Satisfaction by Service Quality and Meeting Package Facilities together can be explained as 69.7%. Keywords: Service Quality, Facilities, Customer Satisfaction